Comparison of Tamsulosin Versus Silodosin for Treatment of Patients with Benign Prostatic Hyperplasia - Abdullah, Omer Dilawar, Rifat Yasmin, Tazaeen Hina Kazmi, Mohammad Ali, Sadia (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the efficacy of drug in improving lower urinary tract symptoms for improved health care and better management of patients. Study Design: Randomized controlled trial Place and Duration of Study: Department of Urology, Department of General Medicine and Department of General Surgery, Pakistan Ordinance Factories Hospital, Wah Cantt from 1st January 2021 to 31st July 2022. Methodology: One hundred patients, age more than 45 years, moderate to severe prostate hyperplasia and prostrate size >50 gm were included. Detailes demographics were recorded after taking informed written consent. Patients were divided into two groups randomly through lottery method. In group A; patients were given tablet Tamsulosin 0.4 mg once daily and in group B; patients were given tablet Silodosin 4 mg once daily for 12 weeks. Effectiveness between both groups were compared. Results: In group A, mean age of 59.70±7.45 years. In group B; mean age of 59.74±7.69 years. In group A; pre-treatment mean IPSS score 16.74±1.78 while in group B; mean score was 16.12±2.46. Pre-treatment PVR in group A was 57.62±8.9 while in group B mean PVR was 57.96±8.71. The post-treatment IPSS score showed that group A mean IPSS score of 9.26±1.61 while group B had mean IPSS score was 6.58±1.26 and P<0001. The post-treatment PVR volume results showed that group A mean PVR volume of 29.5±3.03 while group B had mean PVR was 25.12±1.94 and P<0001. Conclusion: The silodosin is an effective therapy for LUTS in men with benign prostatic hyperplasia. Keywords: Treatment, Benign prostatic hyperplasia, Lower urinary tract symptoms